Sishen Pill inhibits intestinal inflammation in diarrhea mice via regulating kidney-intestinal bacteria-metabolic pathway - Li, Xiaoya; Qiao, Bo; Wu, Yueying; Deng, Na; Yuan, Jiali; Tan, Zhoujin (Frontiers in Pharmacology, 2024)
Background: Sishen Pill (SSP) has good efficacy in diarrhea with deficiency kidney-yang syndrome (DKYS), but the mechanism of efficacy involving intestinal microecology has not been elucidated.Objective: This study investigated the mechanism of SSP in regulating intestinal microecology in diarrhea with DKYS.Methods: Adenine combined with Folium sennae was used to construct a mouse model of diarrhea with DKYS and administered with SSP. The behavioral changes and characteristics of gut content microbiota and short-chain fatty acids (SCFAs) of mice were analyzed to explore the potential association between the characteristic bacteria, SCFAs, intestinal inflammatory and kidney functionrelated indicators.Results: After SSP intervention, the body weight and anal temperature of diarrhea with DKYS gradually recovered and approached the normal level. Lactobacillus johnsonii was significantly enriched, and propionic, butyric, isobutyric and isovaleric acids were elevated. Serum creatinine (Cr), interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) levels of the mice were reduced, while serum blood urea nitrogen (BUN) and secretory immunoglobulin A (sIgA) in the colonic tissues were increased. Moreover, there were correlations between Lactobacillus johnsonii, SCFAs, intestinal inflammatory, and kidney function.johnsonii-propionic acid" pathway, thus achieving the effect of treating diarrhea with DKYS.